Isolation of Primary Mouse Pulmonary Microvascular Endothelial Cells and Generation of an Immortalized Cell Line to Obtain Sufficient Extracellular Vesicles - Liu, Xu; Xia, Feiping; Wu, Xiao; Tang, Ying; Wang, Lu; Sun, Qin; Xue, Ming; Chang, Wei; Liu, Ling; Guo, Fengmei; Yang, Yi; Qiu, Haibo (Frontiers in Immunology, 2021)
Pulmonary microvascular endothelial cells (PMECs) and the extracellular vesicles (EVs) derived from PMECs participate in maintaining pulmonary homeostasis and mediating inflammatory response. However, obtaining high-purity population of PMECs and their EVs from mouse are still notoriously difficult. Here, we provide a protocol to isolate primary mouse PMECs (pMPMECs) and transduce SV40 lentivirus into pMPMECs to establish cell line (immortalized MPMECs, iMPMECs) to collect sufficient EVs. pMPMECs and iMPMECs can be identified by morphologic criteria, phenotypic expression profile (e.g., CD31, CD144, G. simplicifolia lectin binding) and functional characteristics (e.g., Dil-acetylated low density protein uptake, Matrigel-angiogenesis). Further, we identify pMPMEC-EVs and iMPMEC-EVs and compare them. The characteristics of pMPMEC-EVs and iMPMEC-EVs are ascertained by transmission electron microscopy, nanoparticle tracking analysis (NTA) and protein markers (e.g., CD31, CD81 and Tsg101). iMPMECs derive far more EVs than pMPMECs, while the particle size distribution of them is similar. To conclude, our detailed protocol to isolate and immortalize MPMECs enables researchers to deeply investigate their specific roles in pulmonary physiology and diseases.